Analysis of Hand Surgery Questions on Orthopedic In-training Examination From 2014 to 2019. (September 2022) - LeBrun, Drake G.; Premkumar, Ajay; Ellsworth, Bridget; Shen, Tony S.; Cross, Michael B.; Fufa, Duretti T.
Background: The orthopedic in-training examination (OITE) continues to evolve over time. It is important for orthopedic residents and residency programs to have an up-to-date understanding of the content and resources being used on the OITE to study and tailor curricula accordingly. This study presents an updated analysis of the OITE hand domain from 2014 to 2019. Methods: All OITE questions related to hand surgery from 2014 to 2019 were analyzed for topic, subtopic, taxonomy, imaging modalities, and bibliometric factors related to cited references. Results: Of the 1600 OITE questions, there were 113 hand surgery questions (7.1%) over a 6-year period. The most commonly tested topics were nerve (n = 22; 19%), fracture/dislocation (n = 21; 19%), and tendon/ligament (n = 19; 17%). Complex clinical management questions were the most common taxonomic category (n = 66; 58%). Two hundred fifty-two references were cited, the most common of which were from the Journal of Hand Surgery (American Volume) (n = 76; 30%), Journal of the American Academy of Orthopaedic Surgeons (n = 27; 11%), and Hand Clinics (n = 21; 8%). Publication lag decreased over the study period ( P = .009). Twenty-five questions (22%) used imaging modalities, and 21 (19%) used clinical photos. Compared with a prior analysis from 2002 to 2006, there were more questions related to nerves (19.5% vs 9.8%, P = .041). Conclusions: Residents and residency programs can benefit from an updated understanding of OITE hand surgery content and resources. The current analysis identifies high-yield topics and resources that can guide resident preparation for the OITE.